Research Progress on the Restorative Benefits of Plant Color Schemes in Campus Activity Spaces - Zhong, Pengfei (International Journal of Natural Resources and Environmental Studies, 2026)
With the advancement of high-quality higher education, psychological stress and cognitive fatigue among university students have become increasingly prominent issues. Consequently, the "educational" and "recovery" functions of campus environments have emerged as a research focus within the field of landscape architecture. Plant color, as a core visual element in landscape perception, serves as a crucial means for implementing low-cost, non-contact environmental interventions. This paper systematically defines core concepts—plant color classification, restorative environments, and restorative effects—by reviewing domestic and international literature. It analyzes restorative measurement indicators from physiological and psychological dimensions and reviews global research progress on plant color restorative effects in urban, medical, elderly care, and campus settings. Visual analysis using CiteSpace reveals a shift from empirical descriptions toward evidence-based quantitative design. Finally, addressing current gaps—including insufficient segmentation of campus settings, inadequate group adaptability, and lack of regional seasonal studies—this paper proposes future research directions for plant color schemes in university activity spaces, aiming to provide theoretical foundations for creating high-quality educational environments.